Transforming the paradigm of public university leadership into a more political one in emerging nations: a case of Bangladesh - Alam, Gazi Mahabubul (Inderscience, 2023)
Studies have examined the impact of political interference on ˜instructional, ˜constructive and ˜distributed models of leadership. There is not enough evidence on whether the leadership of universities is now a political one, and/or its impacts; that is the subject of this investigation. Considering Bangladesh as a case study, this qualitative study discovered that the public university sector does not appear to follow ˜instructional and ˜constructive models, let alone ˜distributed leadership. Without recognising and utilising an established education leadership model, political leadership does in fact manage the university. This cultivates ˜corruption and ˜nepotism which interfere with real higher education. Innovation of a specialised model for university leadership is consequently particularly suited to emerging nations and well-timed.